Use of NPK Fertilizer for Cultivating Eucheuma spinosum Seaweed at Different Doses on a Laboratory Scale - Nur Yatin; Nunik Cokrowati; Fariq Azhar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Seaweed is a low-level plant whose roots, stems and leaves cannot be distinguished from each other and is better known as a thallus. Seaweed is one of the leading fisheries commodities. This study aims to analyze the growth and carrageenan content of Eucheuma spinosum given Nitrogen, Phosphate and Potassium (NPK) fertilizer at different doses. The method used was an experimental method with a completely randomized design (CRD) consisting of 4 treatmentsa are P0 (control), P1 (2 g/l), P2 (2.5 g/l), and P3 (3 g/l). Each treatment was repeated 3 times. Data were analyzed using ANOVA, then if further tests were carried out, the Duncan test was used. The results showed that seaweed E. spinosum which was maintained for 30 days had a survival rate, final weight, final length and carrageenan yield ranging between 16.1% - 50.1%, 3.23 g - 10.13 g respectively, 10 cm - 17.6 cm and 6.75% - 10.86% with the best treatment, namely at a fertilizer dose of 2.5 g/l, while the best carrageenan yield treatment was found in the control treatment. This study concluded that E. spinosum seaweed given different doses had a real effect on survival and final weight. The highest survival rate and final weight were found in the 2.5 g/l dose treatment, namely 50.6% and 10.13 g, and the control treatment gave a higher yield of carrageenan than the other treatments, namely 10.86%.